PROFIL USAHA OBJEK WISATA TRACKING MANGROVE DESA TRANS PATO’A KECAMATAN HELUMO KABUPATEN BOLAANG MONGONDOW SELATAN (Business Profile of Tracking Mangrove Tourism Objects in Trans Pato'a Village, Helumo District, South Bolaang Mongondow Regency) - Wiro Manileth; Gene H. M. Kapantow; Lyndon R. J. Pangemanan (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
Mangrove forest is one of the tourist attractions in North Sulawesi, including the Mangrove Forest in Trans Pato'a Village. This tourist spot, which is named